If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4q + 9)(4q + 9) = 0 Reorder the terms: (9 + 4q)(4q + 9) = 0 Reorder the terms: (9 + 4q)(9 + 4q) = 0 Multiply (9 + 4q) * (9 + 4q) (9(9 + 4q) + 4q * (9 + 4q)) = 0 ((9 * 9 + 4q * 9) + 4q * (9 + 4q)) = 0 ((81 + 36q) + 4q * (9 + 4q)) = 0 (81 + 36q + (9 * 4q + 4q * 4q)) = 0 (81 + 36q + (36q + 16q2)) = 0 Combine like terms: 36q + 36q = 72q (81 + 72q + 16q2) = 0 Solving 81 + 72q + 16q2 = 0 Solving for variable 'q'. Factor a trinomial. (9 + 4q)(9 + 4q) = 0Subproblem 1
Set the factor '(9 + 4q)' equal to zero and attempt to solve: Simplifying 9 + 4q = 0 Solving 9 + 4q = 0 Move all terms containing q to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4q = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 4q = 0 + -9 4q = 0 + -9 Combine like terms: 0 + -9 = -9 4q = -9 Divide each side by '4'. q = -2.25 Simplifying q = -2.25Subproblem 2
Set the factor '(9 + 4q)' equal to zero and attempt to solve: Simplifying 9 + 4q = 0 Solving 9 + 4q = 0 Move all terms containing q to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4q = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 4q = 0 + -9 4q = 0 + -9 Combine like terms: 0 + -9 = -9 4q = -9 Divide each side by '4'. q = -2.25 Simplifying q = -2.25Solution
q = {-2.25, -2.25}
| 4(x+3)=2x+10+2x | | 46/63-5/7 | | 57+57+123+x=360 | | 5+3(y-4)=5(y+3)-y | | -9+6-12= | | 5+7g=54 | | 12x+17x-6+5=-5x+5-6 | | 63=9(2-w) | | 6-4(5p+9)+3(2+p)=-18 | | 3t-18=4(-3-3/4) | | -6x+5(1)=1 | | 6n=64 | | 4.6x-14.6=5.4 | | 2(n+n+1)=(n+2)-36 | | 3/5x-2=1/5 | | 10y(y+2)+3x=5(3-x) | | 4y-2(x-y)= | | 5x-3x+16=-x+8 | | 9w-8=64 | | 5.50-3.75= | | 8+2x+3-x=2+1 | | (3/x)-2=11 | | J-62/4=5 | | -6x+-9=1 | | 4s-10=6 | | 8k-5= | | 6(w-1)=2w+4-2(-4w-2) | | -4n+7=1 | | 35=4y+y | | 3x+4(x+y)= | | 9+23= | | -3+8=5a+24 |